The dynamic nature of netrin-1 and the structural basis for glycosaminoglycan fragment-induced filament formation - Markus Meier; Monika Gupta; Serife Akgül; Matthew McDougall; Thomas Imhof; Denise Nikodemus; Raphael Reuten; Aniel Moya-Torres; Vu To; Fraser Ferens; Fabian Heide; Gay Pauline Padilla-Meier; et al. (Nature Communications, 2023)
In this work, the authors report that heparin oligosaccharides have a significant impact on the highly dynamic behaviour of netrin-1 by inducing hierarchical and distinct super assemblies leading to unique, yet unknown netrin-1 filament formation.